COBIT: A FRAME WORK FOR DEVELOPING AN EFFECTIVE AUDIT - Pastor Carrasco, Carlos Alberto (2014)
The development of technology is perceived globally as a trigger for permanent changes in the business en-vironment. However, there is one overriding idea that appears immobile against this technological strength which implies that organizations that survive are those that provide more value to their customers.The role of the audit continues to provide assurance services to both internal and external customers. Since the use of technology impacts the way we do business, there must be effective and simple ways to carry out the evaluation of the controls that must exist to ensure that service.The main objective of the research is to determine which methodology should be used to achieve ade-quate control of information technology, risks and vulnerabilities for effective audit process.Our main hypothesis is: The COBIT developed by ISACA is a methodology that should be used to achie-ve adequate control of information technology, risks and vulnerabilities for effective audit process.From the review and research conducted, we conclude that the COBIT, auditors information technology will have a suitable tool that will allow them to meet the new needs of organizations.